Behavior of Sunscreen Usage Among Medical Students - Triana Novitasari; Subur Prajitno; Diah Mira Indramaya (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Photoaging is an early skin aging process caused by sun exposure. Sunscreen is effective as a primary photo-protection to protect the skin from the dangers of ultraviolet radiation (UV) sunlight. However, sunscreen is often used in the wrong manner, so that it can reduce the effectiveness of the work of sunscreen. Purpose: To describe the knowledge and the practice of sunscreen usage among medical students of Universitas Airlangga and find out the relationship between the knowledge and the practice of sunscreen usage. Methods: This study is an analytic-observational study. Data were collected through questionnaire sheets that distributed to medical students of Universitas Airlangga class of 2016, 2017, and 2018. The results were analyzed using the Spearman test with a significance level of 1%. Result: Obtained total respondents that fulfilled the inclusion criteria were 159 respondents, with 88.68% were female and 11.32% were male. Based on Fitzpatrick skin type, 55.97% respondents found with skin type-IV. There were 59.12% respondents got score of knowledge in the medium category and 64.78% respondents got score of practice also in the medium category. Based on analytic statistic correlation test between knowledge and practice of sunscreen usage, known that the significance value is equal to 0,006 with coefficient correlation is equal to 0.216. Conclusion: The knowledge and the practice of sunscreen usage among medical students of Universitas Airlangga is already in a fairly good range. There is a parallel relationship between the knowledge and the practice of sunscreen usage among medical students of Universitas Airlangga but with a low level of correlation strength.